English Air quality management in the development of mining deposits (Journal of Geography and Environmental Management, 2023)
The article provides an overview of modern studies on the assessment of the state and management of the quality of atmospheric air in mining deposits. It is estimated that more than 8,100 ore tailings are formed worldwide with a discharge volume of 10 billion m3. The Global Assessment of Pb-Zn Mineral Resources found that the mining and processing of ore in 67 countries, with an average grade of 0.44% Pb and 1.20% Zn, has given rise to a number of environmental problems, the most acute of which is related to air pollution. However, a large amount of waste from Pb-Zn mines is disposed  without proper management in tailings, which are potentially dangerous due to exposure to oxidants and weather conditions, such as the eolian effect. Numerous studies unequivocally indicate that pollution of the surface layer of the atmosphere is the most powerful, constantly acting factor influencing humans, the food chain and the environment. In industrialized countries, the optimal combination of the amount of atmospheric pollution and the degree of protection against it is the air quality management system, in accordance with the principles of Environmental Impact Assessment. The review describes the existing methods and technologies for managing dust and gas pollution of atmospheric air at mining enterprises. It is shown that when assessing atmospheric pollution, it is advisable to use, instead of individual meteorological elements, complex parameters that characterize a specific meteorological situation and conditions.
Keywords: air pollution, aerosols, tailings, climatic factors, air quality management